Pejoration and Naming of Politicians in Readers’ Comments - Perić Šormaz, Marija (Slavia Centralis, 2024)
Readers’ comments on political events often include a negative evaluation of the speaker and frequent pejorative expressions (cf. Finkbeiner et al. 2016, Perić and Miletić 2019). This type of verbal violence always targets some characteristics of the addressee as described by Havryliv (2009: 35–40): character traits and manner of behavior of the addressee, appearance, physical injuries, age of the addressee, universal swear words with abstract meaning, regional and national insults, and business insults. Politicians are often given creative nicknames or descriptive names through such an evaluation of the speaker, where some of these points are thematized. This paper will investigate the way politicians are named as a form of verbal violence in readers’ comments on political elections. The aim of this research is to determine the way politicians are named and the creation of their nicknames in Croatian and German, and to determine which characteristics of the addressee are most often attacked by such a way of naming.
Keywords: pejoration, evaluation, points of attack, German corpora, Croatian corpora